Di Balik Arena Pertarungan dan Pertaruhan: Historisitas Sabung Ayam Berdasarkan Narasi Sumber Lokal dan Kolonial - Gustaman, Budi (Universitas Hamzanwadi, 2025)
Sabung ayam, or cockfighting, is a game with a long history in the Nusantara region, extending to Southeast Asia. Its implementation has been ongoing since the classical era, continuing to this day, with various applications, including entertainment for kings, religious rituals, public games, and even illegal games. Fighting and betting in the cockfighting arena are narrated periodically in various historical sources, with various changes, uniformity, and diversity in narrative, substance, and perspective that describe conditions in each era. For this reason, this study is significant to question the change in the meaning of cockfighting based on the narrative presented by local and European sources. By using the historical method, this study emphasizes the use of local sources in the form of oral traditions, as well as European sources in the form of ethnographic works, travel notes, colonial government archives, and mass media coverage. In general, this study produces three important findings. First, cockfighting is a game that is often held in the royal environment with a twist of betting based on the narrative of oral tradition. Second, European records interpret cockfighting as a 'national' public entertainment, with the negative stigma of betting that accompanies it. Third, cockfighting became a prohibited game due to the essence of gambling based on colonial legal provisions, and its practice became a form of crime that was widely reported by the mass media. The change in the meaning of cockfighting historically led to the current condition of the problem of criminality in its practice that closely combines aspects of fighting and betting in one unit.